A bridge to justice : the life of Franklin H. Williams - Gort, Enid; Caher, John M. (Fordham University Press, 2022)
Documents the life of a gifted African American leader whose contributions were pivotal to the movement for social justice and racial equalityFranklin Hall Williams was a visionary and trailblazer who devoted his life to the pursuit of civil rights--not through acrimony and violence and hatred but through reason and example. A Bridge to Justice sheds new light on this practical, pragmatic bridge-builder and brilliant, complex individual whose life reflected the opportunities and constraints of an intellectually elite Black man in the twentieth century.Franklin H. Williams was considered a "bridge" figure, someone whose position outside the limelight allowed him to navigate both Black and white circles, span the more turbulent racial waters below, and persuade people to see the world in a new way. During his prolific lifetime, he was a civil rights leader, lawyer, diplomat, organizer of the Peace Corps, United Nations representative, foundation president, and associate of Thurgood Marshall on some of the seminal civil liberties cases of the past hundred years, though their relationship was so fraught with tension that Marshall had Williams sent to California. He worked in the Kennedy and Johnson administrations, served as a diplomat, and became an exceptionally persuasive advocate for civil rights. Even after enduring the segregated Army, suffering cruel discrimination, and barely escaping a murderous lynch mob eager to make him pay for zealously representing three innocent Black men falsely accused of rape, Franklin was not a hater. He believed that Americans, in general, were good people who were open to reason and, in their hearts, sympathetic to fairness and justice.Dr. Enid Gort, an anthropologist and Africanist who conducted hundreds of hours of exclusive interviews with Williams, his family, friends, colleagues, and compatriots, and John M. Caher, a professional writer and legal journalist, have co-written an exhaustively researched and scrupulously documented account of this civil rights champion's life and impact. His story is an object lesson to help this nation heal and advance through unity rather than tribalism.